Exploring the nexus of alliance orientation, ta’awun, and innovation performance: a conceptual analysis for manufacturing SMEs / Hasvenda Noor Abd Rahim and Hasliza Abdul Halim - Abd Rahim, Hasvenda Noor; Abdul Halim, Hasliza (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
SMEs in the manufacturing sector face significant challenges in maintaining innovation performance in the dynamic and complex business environment. Engaging with external partners by maintaining a portfolio of diverse alliances can be a promising strategy to enhance innovation performance.